2004
DOI: 10.2466/pr0.95.6.393-406
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Inventory in Homicidal, Nonaddicted Paranoid Schizophrenic Patients: A Preliminary Study

Abstract: This study assessed the personalities of 13 murderer schizophrenics using Cloninger's Temperament and Character Inventory, controlling different factors such as institution, treatment, detention or loss of liberty, and can discriminate between schizophrenic patients involved in homicide, schizophrenics with no past violent behavior, paranoiac murderers, and imprisoned murderers with no psychiatric history. Results show significantly that murderer schizophrenics had significantly higher scores on the subscale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These studies showed that offenders had significantly higher Novelty Seeking and lower Reward Dependence, Self‐directedness, and Cooperativeness compared with nonoffenders [38,72,73]. Relatively fewer studies have reported similar findings in schizophrenia patients [74], with slight variations. For instance, Jengic et al have reported higher Harm Avoidance and Persistence in addition to higher Novelty Seeking and lower Reward Dependence, Self‐directedness, and Cooperativeness in offender schizophrenia patients compared with the nonoffender counterparts [36].…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that offenders had significantly higher Novelty Seeking and lower Reward Dependence, Self‐directedness, and Cooperativeness compared with nonoffenders [38,72,73]. Relatively fewer studies have reported similar findings in schizophrenia patients [74], with slight variations. For instance, Jengic et al have reported higher Harm Avoidance and Persistence in addition to higher Novelty Seeking and lower Reward Dependence, Self‐directedness, and Cooperativeness in offender schizophrenia patients compared with the nonoffender counterparts [36].…”
Section: Discussionmentioning
confidence: 99%